Urbanization and eco-environment coupling circle theory and coupler regulation - Fang, Chuanglin; Cui, Xuegang; Deng, Xiangzheng; Liang, Longwu (Journal of geographical sciences, 2020)
A near-distance, nonlinear coupling relationship objectively exists between urbanization and the eco-environment. The issue of how to coordinate the relationship between them has become a global strategic and scientific issue. This study reveals the nature, relationship and intensity of coupling between urbanization and the eco-environment from a theoretical perspective. Based on the strength of coupling, relationships can be characterized as having very-low, low, medium, high, very-high or full coupling intensity, which correspond to the categories of random coupling, indirect coupling, loose coupling, cooperative coupling, close coupling, and controlled coupling. Together, these make up an urbanization and eco-environment “coupling tower.” This study also develops an urbanization and eco-environment coupling circle theory and generates 45 coupling graphs (including linear, exponential-curve, logarithmic-curve, double exponential-curve and S-curve graphs) per 10° of rotation of the coupling circle, with different graphs corresponding to different urban development stages and development models. Of the various coupling graphs, the S-curve graph is considered the optimum, as it reflects the best interactivity scenario between urbanization and the eco-environment. Using an S-curve coupling graph, and with the help of an SD model and based on the complex one-to-one, one-to-many, and many-to-many relationships between the variables, this study develops the Urbanization and Eco-environment Coupler (UEC). The UEC is composed of 11 regulating elements and 201 variables. If one variable changes, it changes the whole, affecting the structure, function and regulation of the entire coupler. The UEC includes three spatio-temporal scales: static regulation between multiple urbanization areas and eco-environment areas at the same time, dynamic regulation between the same urbanization area and eco-environment area at different times, and dynamic regulation between multiple urbanization areas and eco-environment areas at different times. Regulation gradually promotes evolution from low-level coupling to high-level coupling between urbanization and the eco-environment.